GOVERNMENT INFORMATION CLARITY AND DIGITAL ENGAGEMENT AS DRIVING FORCES BEHIND DIGITAL RESILIENCE ON THE JEPIN SMART CITY PLATFORM - Meisari, Winda Chelsea; -, Muliawati; Fatimah, Siti (Jurnal Vokasi Indonesia, 2025)
This study examines the influence of information clarity and government digital engagement on the digital resilience of urban communities, using the case study of the Jendela Pontianak Integrasi (JEPIN) platform. The research employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS 7.0, involving 100 respondents from the city of Pontianak. The results indicate that information clarity (β = 0.49; p < 0.001) and government digital engagement (β = 0.37; p < 0.001) have a positive and significant effect on digital resilience. The model demonstrates strong reliability (Composite Reliability: 0.847–0.914; Cronbach’s Alpha: 0.772–0.882), good validity (factor loading > 0.5; AVE > 0.5), and a high level of model fit (GoF = 0.569). The R² value of 0.517 shows that the model explains 51.7% of the variance in digital resilience, while the Q² value of 0.524 indicates predictive relevance. These findings underscore the importance of transparent information and active government engagement in enhancing citizens’ adaptability, problem-solving capacity, and critical digital literacy within the smart city ecosystem.